Assessment of alcohol use and dependence using the WHO alcohol use disorder identification test tool in a fishermen community of Tamil Nadu-a cross-sectional study - Chinnaian Sivagurunathan; Ramesh Anshul; Sankar Karthik; Deepak Avinash KR; Mani Ezhilvanan; Ashokkumar Vikram (Asian Journal of Medical Sciences, 2025)
Background: Alcohol use disorder is a condition where drinking causes harm to an individual’s health and they cannot stop drinking even if it harms them. Previous research has shown that alcohol use and illnesses related to alcohol consumption are high among fishermen compared to any other profession. Aims and Objectives: The aim of the study was to estimate the proportion of harmful alcohol use and probable dependence to alcohol among selected fishermen community in Tamil Nadu and find out the associated sociodemographic factors. Materials and Methods: A community-based cross-sectional study was conducted among fishermen in a coastal village in Chengalpattu district of Tamil Nadu from May to July 2024 using the World Health Organization alcohol use disorder identification test. A house‑to‑house survey was conducted in the study area to identify and include 200 eligible participants. Data were analyzed using SPSS Version 21.0. Results: Out of 200 fishermen, majority (64%) were between 40 and 59 years and 64% were married. Around 49.5% had been in fishing occupation for more than 21 years. About 72.5% of study participants go to sea daily. About 55% of fishermen spent 6–24 h in sea. About 80.5% reported absenteeism due to alcoholism. Majority (62.5%) engaged in harmful use, and 20.5% were likely to be dependent on alcohol. Age group, marital status, education status, duration of occupation, and time spent in sea had statistically significant association with the pattern of alcohol use among the study participants. Conclusion: Alcohol use and dependence is a significantly higher among fishermen in the present study. Community-level awareness campaigns highlighting the detrimental effects of alcohol consumption are crucial to address this problem.